Growth and Physiological Responses of Dendrocalamus asper as Influenced by Different Water Application - Zainol Haida; Ruzana Sanusi; Hafidz Khairul Hisham; Sheriza Mohd Razali; Hazandy Abdul Hamid (BioResources)
Bamboo plantations are in high demand in the global market due to bamboo’s versatility and fast-growing nature. Dendrocalamus asper is one of the important species and is utilized in various industries, making it an economically valuable crop. Increasing yields while maintaining effective cost management is essential for planters. However, water stress possesses a significant challenge which can potentially disrupt bamboo growth and its physiological responses and thus the plant productivity. The objective of this study was to evaluate the growth and physiological responses of D. asper under different water treatments. A total of 45 seedlings were placed in a greenhouse and subjected to three different watering regimes at field capacity. The growth and physiological parameters including culm diameter, plant height, transpiration rate, photosynthesis rate, intercellular carbon dioxide concentration, and stomatal conductance were measured.  The study showed that 100% of water capacity produced the best results for all the growth and physiological parameters measured. The reduction of water significantly reduced the growth of the seedlings, and the increment of water application beyond that point did not contribute to the increment of the plant growth. This indicates that excessive watering of bamboo did not improve growth performance, emphasizing the importance in optimizing water usage and conserving resources for economic sustainability.